Pengaruh Keahlian Audit, Pengalaman, Audit Judgment, dan Situasi Audit Terhadap Ketepatan Pemberian Opini Audit (Studi Empiris Pada Kantor Akuntan Publik yang Terdaftar di IAPI Wilayah DKI Jakarta) - Dahlia Septianingsih, (2021)
This research is using quantitative study aim to see whether there are influence of audit expertise, experience, audit judgment, and audit situation on the accuracy of giving audit opinion. This study uses auditors who work in public accounting firms in the DKI Jakarta area as a sample. Sampling uses a random sampling method with 67 samples auditors who work in public accounting firms in the DKI Jakarta area. Testing the hypothesis in this study was used Multiple Linear Regression Analisys using SPSS analysis tool with a significant level of 0.05 %. The results of these tests indicate that (1) there is a significant effect between audit expertise on the accuracy of giving audit opinion, (2) there is a significant influence between experience on the accuracy of giving audit opinion, (3) there is a significant influence between audit judgment on the accuracy of giving audit opinion, and (4) there is no significant effect between the audit situation on the accuracy of giving audit opinion.